Polyvictimization and developmental trauma in childhood - Julian D. Ford (European Journal of Psychotraumatology, 2021)
Background: Polyvictimization (Gilbar & Ford, ) and developmental trauma (van der Kolk, Ford, & Spinazzola, ) have been identified in the past decade as empirically operationalized high impact forms of cumulative childhood trauma (Ford, ). Childhood polyvictimization (PV) is defined as experiencing multiple types of interpersonal victimization sequentially or concurrently at any point in childhood (lifetime) or in the past year (recent). Childhood developmental trauma (DT) is defined as a combination of traumatic interpersonal victimization and disruption in attachment bonds with primary caregiver(s). Objective: To present an overview of research findings to date and a systematic agenda for research on polyvictimization and developmental trauma over the next decade. Method: A systematic review of research on polyvictimization and developmental trauma in childhood was conducted in peer-reviewed publications from 2010 to 2020. Results: More than 100 empirical studies of PV or DT were reviewed. Childhood PV was associated with both the risk and severity of internalizing and externalizing disorders, specifically with PTSD when victimization is sufficiently severe to be traumatic. Childhood DT was associated with dysregulation in three domains (affective/physiological, attentional/behavioural, self/relational) that can be reliably and validly assessed with 15 symptoms that are distinct from the symptoms of ICD-11 PTSD and complex PTSD (see ).Table 1. Developmental trauma disorder (DTD) symptoms Emotion or somatic dysregulationo B1: Emotion dysregulation (either B1.a. extreme negative affect states; or B1.b. impaired recovery from negative affect states)o B2: Somatic dysregulation (either B2.a. aversion to touch; or B2.b. aversion to sounds; or B2.c. somatic distress/illness that cannot be medically explained/resolved)o B3: Impaired access to emotion or somatic feelings (either B3.a. absence of emotion; or B3.b. physical anaesthesia that cannot be medically explained/resolved)o B4: Impaired Emotion or Somatic Verbal Mediation/Expression (either B4.a. alexithymia; or B4.b. impaired ability to recognize/express somatic feelings/states)Attentional or behavioural dysregulationo C1: Attention bias towards or away from threat (either C1.a. threat-related rumination; or C1.b. hyper- or hypo-vigilance to actual or potential danger)o C 2: Impaired self-protection (either C2.a. extreme risk-taking or recklessness; or, C2.b. intentional provocation of conflict or violence)o C 3: Maladaptive self-soothingo C4: Non-suicidal self-injuryo C5: Impaired ability to initiate or sustain goal-directed behaviourRelational- or self-dysregulationo D1: Self-loathing, including self viewed as irreparably damaged and defectiveo D 2: Attachment insecurity and disorganization (either D2.a. parentified over-protection of caregivers; or D2.b. difficulty tolerating reunion following separation from primary caregiver(s))o D 3: Betrayal-based relational schemas (either D3.a. expectation of betrayal; or D3.b. oppositional-defiance based on expectation of coercion or exploitation)o D4: Reactive verbal or physical aggression (including proactive instrumental aggression that is motivated primarily by preventing/responding to harm/injury)o D5: Impaired psychological boundaries (either D.5a. promiscuous enmeshment; or D5.b. craving for reassurance)o D6: Impaired interpersonal empathy (either D6.a. lacks empathy for, or intolerant of, others’ distress; or D6.b. excessive responsiveness to the distress of others) Research is needed to prospectively determine, within and across the developmental epochs of childhood and adolescence: (1) how the specific types of traumatic victimization in PV and DT differ or remain constant; (2) if and how PV and DT co-occur or diverge both on a linear and a quadratic basis; (3) the form and timing/sequencing of the separate and shared biopsychosocial sequelae of PV and DT; (4) the association of PV and DT with diagnoses of internalizing (including PTSD/cPTSD) and externalizing disorders, and severe comorbidities (e.g., self-harm, school failure, juvenile delinquency, medical illness); (5) protective factors and resilience and recovery trajectories; (6) short- and long-term response to evidence-based psychotherapies and mediators/mechanisms of symptom and impairment reduction. Conclusions: Polyvictimization and developmental trauma operationalize the broad construct of complex trauma, and parallel but are, respectively, more comprehensive and more attachment/relationally focused than the adverse childhood experiences construct.